2021
DOI: 10.1093/brain/awab052
|View full text |Cite
|
Sign up to set email alerts
|

ATP1A2- and ATP1A3-associated early profound epileptic encephalopathy and polymicrogyria

Abstract: Constitutional heterozygous mutations of ATP1A2 and ATP1A3, encoding for two distinct isoforms of the Na+/K+-ATPase (NKA) alpha-subunit, have been associated with familial hemiplegic migraine (ATP1A2), alternating hemiplegia of childhood (ATP1A2/A3), rapid-onset dystonia-parkinsonism, cerebellar ataxia-areflexia-progressive optic atrophy, and relapsing encephalopathy with cerebellar ataxia (all ATP1A3). A few reports have described single individuals with heterozygous mutations of ATP1A2/A3 associated with sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 76 publications
(58 reference statements)
0
34
0
Order By: Relevance
“…Mutations in ATP1A2 have been described in FHM2 and AHC1. These neurological disorders are dominantly inherited and are primarily caused by missense mutations (Chatron et al, 2019;Vetro et al, 2021). L764P, W887R, M731T, R689Q, D718N, P979L, E174K, C515Y, I286T, and T415M mutations occurred in families with FHM2 (De Fusco et al, 2003;Jurkat-Rott et al, 2004;Todt et al, 2005;Vanmolkot et al, 2003;Vanmolkot et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in ATP1A2 have been described in FHM2 and AHC1. These neurological disorders are dominantly inherited and are primarily caused by missense mutations (Chatron et al, 2019;Vetro et al, 2021). L764P, W887R, M731T, R689Q, D718N, P979L, E174K, C515Y, I286T, and T415M mutations occurred in families with FHM2 (De Fusco et al, 2003;Jurkat-Rott et al, 2004;Todt et al, 2005;Vanmolkot et al, 2003;Vanmolkot et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Target enrichment kits, sequencing platforms, data analysis, and WES statistics are reported in Supplementary Table 2-6 and in the Supplementary Methods. WES data processing, read alignment to the GRCh37/hg19 version of genome assembly, and variant filtering and prioritization by allele frequency, predicted functional impact, and inheritance models were performed as previously reported [76][77][78][79][80] . WES data output is summarized in Supplementary Table…”
Section: Exome Sequencing Analysismentioning
confidence: 99%
“…PMG PMG is the most common developmental malformation of the cerebral cortex, characterised by abnormal folding and laminar organisation. Recently, de novo and familial mutations in ATP1A3 were found in patients affected by a severe form of PMG characterised by epilepsy and a global developmental delay (Miyatake et al, 2021;Smith et al, 2021;Vetro et al, 2021). PMG mutations include D801N, the most common mutation in AHC (Panagiotakaki et al, 2015), and L924P, which is also observed in early infantile epileptic encephalopathy (EIEE) (Arystarkhova et al, 2019).…”
Section: Capos Syndromementioning
confidence: 99%
“…A variety of mutations affecting the aspartic acid at position 801 (D801) can cause RDP, AHC or PMG. D801E and D801V are AHC-causing mutations (Panagiotakaki et al, 2015), whereas D801N can cause AHC and PMG (Panagiotakaki et al, 2015;Vetro et al, 2021), and D801Y can cause RDP and AHC (de Carvalho Aguiar et al, 2004;Viollet et al, 2015). Homozygous Atp1a3 D801Y mice die neonatally.…”
Section: Atp1a3 D801ymentioning
confidence: 99%